Optimalisasi Sistem Informasi Administrasi Desa Melalui Pelatihan Microsoft Excel Dan Google Workspace Bagi Aparatur Pemerintahan Desa Sanankerto, Kabupaten Malang - Mohammad Syafriel; Novy Karmelita Indrawati; Roni Angger Aditama; Gusnar Mustapa; M. Shabry (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Sanankerto Village still relies on manual administration, which affects the efficiency of data management and public services. This community service program aims to optimize the village administrative information system through training in Microsoft Excel and Google Workspace for 20 village officials. The methods used include lectures, demonstrations, hands-on practice, and one-month mentoring. Evaluation results show a significant increase in skills—the average pre-test score of 50% rose to 85% in the post-test. Participants are now able to prepare financial reports, use spreadsheets for archiving, and utilize Google Docs and Google Drive for collaborative village data management. These findings align with similar community programs in Kedondong District, where Excel has been used for systematic administrative archiving. Moreover, the use of Google Spreadsheet has proven to enhance organizational efficiency in the Karang Taruna youth organization. This program demonstrates that strengthening village officials' capacity in information technology can support more professional and accountable village governance.